Revisiting Institutional/Occupational Model in Turkish Military - Adem Başpınar (İstanbul Üniversitesi Sosyoloji Dergisi)
This article questions the applicability of Moskos’ institutional/occupational model in a non-Western country whose modernization process resembles that of Western countries. This may be important for two reasons: First, most military sociologists have based their theories on the military’s position and development in Western societies. Whether the historical military development in Turkey resembles Western militaries due to the 19th-century military modernization efforts through Western experts’ guidance with the military as leader in the nation’s modernization or whether this historical military development had a unique structure and mission involving founding the country is debatable. Second, most existing studies on the Turkish military and civil-military relations in Turkey have been conducted by journalists, political scientists, and historians and lack a background in sociological theory. Instead, these studies have discussed the direct or indirect interventions of armed forces in politics. This paper begins building the theoretical foundation for a discussion of the opportunities and challenges of reorganizing Turkey’s civil-military relations by examining the applicability of one Western model to this non-Western country.